Pengaruh Substitusi Limbah Keramik dan Superplasticizer terhadap Peningkatan Kuat Tekan Beton - Englan Agung Gumelar; Yudi Setio Prabowo (Institut Teknologi Garut, 2026)
This study aims to analyze the effect of using ceramic waste as a partial substitute for coarse aggregate on the compressive strength of concrete, as well as the role of superplasticizer addition in improving concrete quality. A laboratory experimental method was conducted using ceramic waste variations of 5% and 10% of the total coarse aggregate weight, both without and with superplasticizer. Cube-shaped specimens measuring 15 × 15 × 15 cm were produced with a planned concrete strength of fc = 20 MPa and tested at the ages of 7, 14, 21, and 28 days using a Compression Testing Machine. The test results indicate that the substitution of ceramic waste without additives reduced the compressive strength of concrete, whereas the combination of ceramic waste and superplasticizer significantly improved compressive strength. The variation containing 10% ceramic waste combined with superplasticizer achieved the highest compressive strength of 22.4 MPa at 28 days, surpassing normal concrete. Practically, this study provides a potential alternative for utilizing ceramic waste in the construction industry to reduce solid waste volume while producing more efficient and environmentally friendly concrete mixtures. Theoretically, these findings enrich the study of the interaction between ceramic-based recycled aggregates and superplasticizers in enhancing the density and mechanical performance of concrete. Therefore, ceramic waste can be recommended as a substitute for coarse aggregate up to 10% when combined with superplasticizer to produce concrete that is strong, economical, and supportive of sustainable construction principles.